Mass and Energy Flows of Cardoon Oil in a Prototype System for Seeds Milling and Vegetable Oil Treatment and Cogeneration. (December 2015) - Cavalaglio, Gianluca; Petrozzi, Alessandro; Coccia, Valentina; D'Antonio, Silvia; Cotana, Stefano
Abstract: The experimentation was carried out in a prototype for the production of vegetable oil from seeds. The system consists of seeds storage, mill, filtration system, oil tanks and diesel engine for combined heat and power production. The vegetable oil tested is cardoon oil; cardoon biomass is the main topic of BIT3G project, that aims to develop biorefineries integrated in the territory through the use of biomass residues or sustainable energy crops (cardoon, black locust, miscanthus) in marginal lands. In this study the milling step was monitored in order to evaluate mass and energy flows; input biomass was separated into biomass residues and seeds, and each part was evaluated in terms of mass, moisture, low heating value. The milling products, vegetable oil and solid panel, were evaluated in terms of mass, moisture and energy content, estimating oil efficiency in the press and main characteristics. Finally an energy balance was performed monitoring the process energy consumption and energy potential using all obtained products, oil, panel and residues for power, heat and cooling purposes.